2022
DOI: 10.2147/opth.s379484
|View full text |Cite
|
Sign up to set email alerts
|

Systane iLux Thermal Pulsation System in the Treatment of Meibomian Gland Dysfunction: A Post-Hoc Analysis of a 12-Month, Randomized, Multicenter Study

Abstract: This study aimed to demonstrate the effectiveness of Systane iLux, a thermal pulsation device, in patients with MGD, over 12 months post-single treatment. Methods: This is a post-hoc analysis of a previous prospective, assessor-masked, parallel-group, multicenter study (NCT03956225) that compared the effectiveness and safety of iLux with LipiFlow in subjects with MGD. The original study included subjects with meibomian gland score (MGS) ≤12 in lower eyelids, Impact of Dry Eye on Everyday Life-Symptom Bother (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The ILux ® MGD Thermal Pulsation System is a handheld inoffice device that allows the application of localized heat and pressure while simultaneously visualizing the MGs. Previous studies have demonstrated the ability of ILux ® to alleviate signs and symptoms of dry eye in patients with MGD until one year [20,22,34] . Our study showed that one treatment session with ILux ® and five sessions of manual expression significantly reduced the signs and symptoms of MGD.…”
Section: Ilux ® Compared To Mechanical Meibomian Gland Expressionmentioning
confidence: 99%
“…The ILux ® MGD Thermal Pulsation System is a handheld inoffice device that allows the application of localized heat and pressure while simultaneously visualizing the MGs. Previous studies have demonstrated the ability of ILux ® to alleviate signs and symptoms of dry eye in patients with MGD until one year [20,22,34] . Our study showed that one treatment session with ILux ® and five sessions of manual expression significantly reduced the signs and symptoms of MGD.…”
Section: Ilux ® Compared To Mechanical Meibomian Gland Expressionmentioning
confidence: 99%
“…These sensors automatically turn off the light-emitting diodes when the inner and outer eyelid temperatures exceed 44°C and 45°C, respectively. 68,69 This device has been documented to clear meibomian gland obstruction and improve dry eye symptoms. 58,[62][63][64][65][68][69][70] The comparative evaluation of LipiFlow and Systane iLux showed that both treatments significantly improved the signs and symptoms of MGD from baseline to 4 weeks.…”
Section: Devicesmentioning
confidence: 99%
“…68,69 This device has been documented to clear meibomian gland obstruction and improve dry eye symptoms. 58,[62][63][64][65][68][69][70] The comparative evaluation of LipiFlow and Systane iLux showed that both treatments significantly improved the signs and symptoms of MGD from baseline to 4 weeks. The 2 treatments had no statistically significant differences for all effectiveness measures.…”
Section: Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…4. However, the aforementioned benefits of thermal pulsation procedures were not prominent in a study conducted in 2020(206)(207)(208)(209)(210). IPL can improve the lipid layer grade, TBUT, tear film osmolarity, OSDI, and visual analog scale symptom scores.• Contact lens-related dry eye: Improvements were observed in the OSDI score, tear quality, and meibomian gland quality.2.…”
mentioning
confidence: 99%